2018
DOI: 10.18535/jmscr/v6i2.156
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and antibiogram of Pseudomonas aeruginosa in Chronic Suppurative Otitis Media (CSOM)

Abstract: Background: CSOM is the most common notorious infection seen in developing countries which has led to a number of serious life threatening complications. The most common organism isolated in CSOM is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Ciprofloxacin displayed a substantial sensitivity rate of 90.91%, and Amoxicillin-clavulanic acid had a lower sensitivity rate of 77.27%. In agreement, Soumya et al [16] revealed that for Pseudomonas aeruginosa, penicillin, piperacillin, and tazobactam were the most effective antibiotics. On the other hand, Kombade et al [17] These findings suggest that Amikacin, Ceftriaxone, Gentamicin, Imipenem, and Vancomycin exhibited varying degrees of effectiveness against S. aureus strains, while Azithromycin and Colistin showed no sensitivity.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Ciprofloxacin displayed a substantial sensitivity rate of 90.91%, and Amoxicillin-clavulanic acid had a lower sensitivity rate of 77.27%. In agreement, Soumya et al [16] revealed that for Pseudomonas aeruginosa, penicillin, piperacillin, and tazobactam were the most effective antibiotics. On the other hand, Kombade et al [17] These findings suggest that Amikacin, Ceftriaxone, Gentamicin, Imipenem, and Vancomycin exhibited varying degrees of effectiveness against S. aureus strains, while Azithromycin and Colistin showed no sensitivity.…”
Section: Discussionmentioning
confidence: 54%
“…Out of the total 100 samples, 6 samples [6%] showed no growth. Candida, E. coli, S. aureus, Pseudomonas aeruginosa, and Klebsiella pneumoniae were detected in 16% [16], 18% [18], 26% [26], 22% [22], and 12% [12] of cases, respectively. In agreement, Sah et al [6] noted that, it was found that Staphylococcus aureus [42.24%] was the most common bacterium isolated in the research, followed by Pseudomonas aeruginosa [28.44%], Klebsiella pneumoniae Sensitivity to amikacin was observed in 60% of the included patients.…”
Section: Discussionmentioning
confidence: 99%